The Effectiveness of Power Point Media in writing skills of Hanzi 汉字 students at class VIII in Private Middle School of Makassar - Azizah, Mir'ah (Universitas Negeri Makassar, 2023)
This research is experimental research (quasi experimental), which has 2 variables, namely power point media as the independent variable, namely writing 汉 字 hanzi as the dependent variable. The population of this study was 209 class VIII students at private junior high schools in Makassar. The sample used random sampling in this study was class VIII A students at private junior high schools in Makassar, totaling 20 students as the control class and class VIII B students at private junior high schools in Makassar. , totaling 20 students as an experimental class. This research data was obtained through a hanzi writing test and analyzed using the T test. H1: The use of power point media is effective in the hanzi writing skills of class VIII students at private junior high schools in Makassar, accepted. H0: The use of power point media is not effective in the Hanzi 汉字 writing skills of class VIII private junior high school students in Makassar, rejected. The results of this study show that tcount is greater than ttable (13.47> 2.03) with a significance level of 0.05. This means that the use of PowerPoint slide media is effective in writing 汉字hanzi for class VIII students at private junior high schools in Makassar. Keywords : Effectiveness, Power Point Media, Writing skill, Hanzi.